Analysis of social media use among Australian and New Zealand otolaryngologists. Issue 6 (22nd October 2018) - Baird, Samantha M.; Marsh, Philip A.; Lawrentschuk, Nathan; Smart, Philip; Chow, Zenia
Abstract : Background: Social media's rapid worldwide growth has permeated surgical practice. To date, no study has evaluated social media use amongst Australian and New Zealand otolaryngologists. Methods: Cross‐sectional study of all members of the Australian and New Zealand Societies of Otolaryngology Head and Neck Surgery with comprehensive searches of websites and social media platforms (Facebook, Twitter, LinkedIn, ResearchGate and Instagram) was performed. Results: A total of 498 otolaryngologists were identified with 81.7% working in Australia; 79.1% had some form of online presence – either professional website or activity on ≥1 social media platform and 53.0% of otolaryngologists had a professional website and mean number of social media profiles averaged 1.35 per surgeon. LinkedIn was the most widely used social media platform (51.6%). 38.8% of otolaryngologists had Facebook accounts with 11.9% of those 'public' accounts used for business purposes. Otolaryngologists with a research and authorship interest had the highest mean number of social media accounts (1.78) and were more likely to be associated with ResearchGate, LinkedIn and website ownership. Facial plastic surgeons averaged the second highest mean number of social media accounts per surgeon (1.71) and were most active on Facebook, Instagram and YouTube. There was a linear decline in the mean number of social media accounts per surgeon and rate of professional website ownership with increasing years in practice. Conclusion: Social media uptake amongst otolaryngologists appears consistent with colleagues in other surgical specialties. Otolaryngologists with fewer years in practice and specialty interests in facial plastic surgery and authorship and research are significantly more active on social media.